The Meaning of Green Light in The Great Gatsby Based on Consumerism Perspective: Umberto Ecos Semiotic Study - Maria Vincentia Eka Mulatsih (Journal of Language and Literature, 2015)
One of recent problems in our country is the habit of being consumerist buying things whichare not needed to update the trend. Some people think that it is not a big problem, but some do not.Avoiding its negative effect is the answer to this problem. This can be done through learning pastexperiences in the literary works, in this case Fitzgeralds novel. The Great Gatsby depicts not onlylove but also consumerism. Through analyzing the sign of green light using Umberto Ecos semiotictheory, we can see the bad effect of consumerism in the past and anticipate it for our future byapplying its oppositional structure. The sign of green light is not merely an orgiastic feature. It is atool for Fitzgerald to fight consumerism effect.